Expert systems for engineers - Siddall, James N. (Marcel Dekker, 1990)
Siddall (engineering, McMaster Univ., Hamilton, Ontario) argues that engineers are perfectly capable of writing their own expert system computer programs, drawing on their pre-existing knowledge of languages such as FORTRAN and PASCAL, their expertise of the engineering method, their experience with.